Efektivitas Blended Learning Berbasis Quided Inquiry Terhadap Penguasaan Konsep Dan Kemampuan Berpikir Kreatif Mahasiswa Pada Mata Kuliah Anatomi Fisiologi Manusia : (The Effectiveness of Blended Learning Based Quided inquiry on The Mastery of Concepts and The Ability of Creative Thinking of Students in a Course Anatomy Human Physiology) - Rahmawida Putri; Nuriyatul Fhatonah (BIODIK, 2021)
The purpose of this research is to 1) know the effectiveness of learning blended learning-based quided inquiry on the ability of the mastery of the concept of the student, and 2) determine the effectiveness of learning blended learning-based quided inquiry on the creative thinking skills of students. The study included 71 students as the sample of the study through random sampling derived from semester II Undergraduate Programs of Pharmacy in the college of Pharmacy Muhammadiyah Tangerang with the category of Class A as the control class and Class B as the experimental class. The draft design of the study using the method of Quasi Experiment Preetest-Posttest Control Group Design. Collecting data using test essay question and questionnaire, and data analysis using statistical parametric t-test with a significance level of 0.05. From the results of Anova test found that the results of the data 0.000 < 0.05, which shows the learning blended learning-based quided inquiry is effective against student mastery of concepts with the results of N-Gain in the control group amounted to 40.6% with the category of less effective and the experimental class of 68.8% with the category quite effective. Learning blended learning-based quided inquiry is effective against the ability of creative thinking of students on the aspects of fluency by 71%, originality by 75%, and the elaboration of 75% including both categories, while on the aspect fleksibility included in the very good category with a percentage of 81%. From the results of the questionnaire responses of students towards learning blended learning-based quided inquiry included in the very good category with an average value of 82,71. Abstrak. Tujuan dari penelitian ini untuk 1) mengetahui keefektivan pembelajaran blended learning berbasis quided inquiry terhadap kemampuan penguasan konsep mahasiswa, dan 2) mengetahui keefektivan pembelajaran blended learning berbasis quided inquiry terhadap kemampuan berpikir kreatif mahasiswa. Penelitian ini melibatkan 71 mahasiswa sebagai sampel penelitian melalui random sampling yang berasal dari semester II Program Sarjana Farmasi di Sekolah Tinggi Farmasi Muhammadiyah Tangerang dengan kategori Kelas A sebagai kelas kontrol dan Kelas B sebagai kelas eksperimen. Rancangan desain penelitian menggunakan metode Quasi Experiment Preetest-Posttest Control Group Design. Pengumpulan data menggunakan tes soal essay dan angket, dan analisis data menggunakan statistik parametrik uji-t dengan taraf signifikansi 0,05. Dari hasil uji Anova diperoleh bahwa hasil data 0,000 < 0,05 yang menunjukkan pembelajaran blended learning berbasis quided inquiry efektif terhadap penguasaan konsep mahasiswa dengan hasil N-Gain pada kelompok kontrol sebesar 40,6% dengan kategori kurang efektif dan kelas eksperimen sebesar 68,8% dengan kategori cukup efektif. Pembelajaran blended learning berbasis quided inquiry efektif terhadap kemampuan berpikir kreatif mahasiswa pada aspek fluency sebesar 71%, originality sebesar 75%, dan elaboration sebesar 75% termasuk kategori baik, sedangkan pada aspek fleksibility termasuk ke dalam kategori sangat baik dengan persentase 81%. Dari hasil angket tanggapan mahasiswa terhadap pembelajaran blended learning berbasis quided inquiry termasuk dalam kategori sangat baik dengan nilai rata-rata 82,71.